The limits of retirement social protection - Romo, Noelia Morales (FCL-UNESP Laboratório Editorial, 2010)
This article presents an analysis of options and alternatives related to retirement in Spain during a global economic crisis. By dealing with qualitative and quantitative data we formulate answers to prior questions related to retirement social protection. We address four main topics: pension coverage, related mainly to the sum and benefi ciaries; age, by focusing on the moment of retirement; the need for an early retirement or the possibility of postponing the age of compulsory retirement; the fi nancing of the pensions system through public funds or private pension plans, and, fi nally, we raise questions on the future of retirement pensions. Last, we provide some clear conclusions about the questions raised.